1991
DOI: 10.1093/brain/114.2.979
|View full text |Cite
|
Sign up to set email alerts
|

CNS Pathology in the Neurological Mutant Rats Zitter, Tremor and Zitter-Tremor Double Mutant (Spontaneously Epileptic Rat, Ser)

Abstract: The pathological alterations in the central nervous system (CNS) were examined in three kinds of mutant rat; the zitter (zi/zi; Zi), the tremor rat (tm/tm; Tm) and the spontaneously epileptic rat (SER) which is a double mutant carrying both zitter and tremor genes. Two major alterations demonstrated in these mutants were hypomyelination and vacuolation or spongy degeneration. Hypomyelination was observed predominantly in SER and to a lesser extent in Zi, and was accompanied by a redundant or aberrant myelin sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Animal models with inactivated ASPA have proved useful in the study of this condition, as with the knockout mouse that was shown to have morphologically abnormal myelin [5]. Similarly, the tremor rat, employed in this study, which possesses a natural ASPA mutation, was shown to have hypomyelination, vacuolation along with spongy degeneration of white matter [26], and in addition loss of oligodendrocytes [27]. Use of these animals as research tools has opened a valuable window for study of the specific contributions of ASPA-mediated acetyl formation to myelin lipid synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…Animal models with inactivated ASPA have proved useful in the study of this condition, as with the knockout mouse that was shown to have morphologically abnormal myelin [5]. Similarly, the tremor rat, employed in this study, which possesses a natural ASPA mutation, was shown to have hypomyelination, vacuolation along with spongy degeneration of white matter [26], and in addition loss of oligodendrocytes [27]. Use of these animals as research tools has opened a valuable window for study of the specific contributions of ASPA-mediated acetyl formation to myelin lipid synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…This observation suggested that the severity of vacuolization correlates with the expressed levels of Atrn mRNA and indicated Atrn mRNA was found widely distributed throughout the CNS; a very high level of expression was observed in the olfactory system, some limbic structures, brain stem, cerebellum, and spinal cord in rats (Lu et al, 1999). Severe vacuolization was found in the brain stem, cerebellum, and spinal cord, whereas less mild lesions were observed in the olfactory system and hippocampus in both the rat mutants Atrn mv /Atrn mv and Atrn zi /Atrn zi (Kondo et al, 1991a(Kondo et al, , 1991b(Kondo et al, , 1992. Although the Atrn mRNA expression pattern and the severity of vacuolization are roughly matched, some differences existed in particular regions of the CNS.…”
Section: Discussionmentioning
confidence: 94%
“…In order to address this possibility with our polyclonal ASPA antibodies, we tested antibody binding to brain and kidney tissues from the Tremor rat, an ASPA-null mutant (Kondo et al, 1991) (see section 3 below). This mutant lacks the entire ASPA gene sequence, so no ASPA protein is produced.…”
Section: Naa Catabolismmentioning
confidence: 99%
“…Tremor rats exhibit muscular tremors starting at about 2 weeks of age, which give way to absence-like seizure activity in later development. Pathology in the CNS involves white matter spongiform degeneration and hypomyelination (Kondo et al, 1991). Similarly, homozygous ASPA −/− knockout mice exhibit subcortical and white matter vacuolation.…”
Section: Naa and Canavan Diseasementioning
confidence: 99%